Advanced Direct Internal Reforming Concepts for Solid Oxide Fuel Cells Running with Biogas. (30th May 2017) - Tran, Dang Long; Kubota, Atsushi; Sakamoto, Mio; Tran, Quang Tuyen; Sasaki, Kazunari; Shiratori, Yusuke
Abstract : For the enhancement of the performance and thermo-mechanical stability of solid oxide fuel cell (SOFC) fueled by biogas (CH4 -CO2 mixture), direct internal reforming (DIR) concepts with gas-barrier mask and in-cell reformer were proposed. Power generation characteristics and thermally-induced stresses of anode-supported cells (ASCs) with these DIR concepts were numerically evaluated by means of CFD modeling. For precisely estimating the net consumption and production rates of gaseous species involved in the internal reforming, the dry and steam reforming of CH4 were simultaneously considered using approximation approaches of artificial neural network (ANN) and fuzzy inference system (FIS). The present calculations revealed the positive effects of the proposed concepts, especially for the ASCs with thinner anode substrate.